Tìm hiểu thơ Xuân Diệu qua nghệ thuật sáng tạo tứ thơ - Vũ Thị Thu Hương (Tạp chí Giáo dục, 2023)
The article studies the art to create poetical ideas in Xuan Dieu’s poems. It focuses on two kinds of poetical ideas, one of which is originated from life and the other from system of artistic thoughts by the author. Poetical ideas reflect the author’s talent in the process of creating poems, the way to discover reality and the ability to generalize, points of view and the taste for beauty of the poet.